Mineral Content of Grass (Cenchrus Ciliaris Linn.) and Grass-Legume Mixtures in Various Intercropping Systems - Singh, Mahander; Singh, R P (Annals of Arid Zone, 2016)
In a field experiment carried out for three consecutive kharif seasons (1981-1983), the mixtures of C. ciliaris and annual fodder and grain legumes exhibited higher nutrients (N, P, K, Ca and Mg)content and their uptake than the pure stand of C. ciliaris. Higher content and uptake of these nutrients were recorded in grass plus fodder legumes than grass plus grain legumes. The grass-cluster bean mixture showed better nutrient content and their uptake followed by the grass-moth bean mixture.